Surface modification of Kapton polyimide by oxygen plasma using a DC Ion shower system - Ty, Jennifer T. Damasco (2012)
To improve the wettability and adhesion properties of Kapton polymide, its surface modification with oxygen plasma using a retrofitted DC ion shower system was studied. The effects of three experimental factors? accelerating voltage, exposure time, and chamber pressure to the surface modification were analyzed using a 23 full factorial design. Characterization by contact angle analysis, ATR-FTIR, AFM, and XPS were carried out to determine the physical and chemical modifications to the polyimide surface.Contact angle analysis showed up to 80.4% decrease in contact angle, treatment A reduced the contact angle of the untreated polyimide from 68.4° to 13.4°. The smallest decrease is by treatment (1) where the contact angle decreased to 36.1° corresponding to a 47.15 decrease. With ANOVA, the interaction between accelerating voltage and chamber pressure was determined to be significant. The anti-synergistic effect between accelerating voltage and chamber pressure which leads to more scattering of the ions prior to hitting of the polymer surface. Another possibility is the overtreatment of the surface where excessive oxidation and bond scission leads to the formation of low-molecular-weight oxidized molecules (LMWOM) and crosslinking. ATR-FTIR analysis shows a small peak around 1010cm-1 corresponding to a C-O stretch to be more prominent in the treated polyimide samples as compared to the untreated polyimide. It indicates that C-O concentration increased after oxygen plasma treatment. The decrease in intensity of the peaks observed for most of the samples indicate the degradation of polyimide structure and the presence of structure defects. AFM analysis showed that some treatments increased the surface roughness while others decreased it. For surfaces with higher roughness after treatment, a few but large surface features are developed. On the samples that had a lower surface roughness after treatment, the number of surface features increased but they are finer. ANOVA showed that the two of the main effects are significant-the accelerating voltage and the exposure time. All 2-factor interaction effects were also found to be significant.The interaction between accelerating voltage and exposure time is a result of selective ablation which is emphasized at shorter exposure times. Longer exposure times yield smoother surfaces as a result of more uniform bombardment of ions. The interaction between accelerating voltage and pressure can be explained by possible difference in energy gradients across the cross-section perpendicular to the ion beam as well as the higher degree of scattering when high setting of chamber pressure is used. The small change in roughness at the low setting of chamber pressure and the relatively larger change in surface roughness at the high setting of chamber pressure may have been because the critical number of ions may not have been reached at the low setting. XPS analysis studied the atomic composition of carbon and oxygen on the polymer surface. After treatment, the O/C ration of the surface is shown to be larger than that of the untreated indicating the formation of oxygen functional groups. The amount of C-O and C=O bonds on the surface increased while that of the C-N decreased. Increase in the C-C is indicative of carbonization and branching of the polymer.
Thesis (M.S. Materials Science and Engineering)--University of the Philippines Diliman.
Keywords: Polyimides; Attenuated total reflectance FTIR Spectroscopy (ATR-FTIR).; Atomic force microscopy (AFM).; X-ray photoelectron spectroscopy (XPS).